Performance analysis of rank reduction estimator in the presence of unexpected modeling errors - WANG Ding; WU Ying (Tongxin xuebao)
A performance analysis of the RARE was presented in presence of unexpected modeling errors.First,the closed-form expression of direction-finding（DF） error was given through the first-order Taylor series expansion of the spatial spectrum function,and then the mean square error（MSE） and DF success probability of the RARE were derived.The numerical experiments,which were associated with the RARE of mutual coupling self-calibration for uniform array,were conducted to validate the theoretical analysis.